PENGARUH MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN BERBICARA MELALUI BERITA SISWA FASE D DI SMP NEGERI 25 KOTA JAMBI - Nadya Rahma Putri; Sophia Rahmawati; Siti Enik Mukhoiyaroh Bambang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of audiovisual media on students' speaking skills in delivering news among seventh-grade students at SMP Negeri 25 Kota Jambi. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 26 students selected through purposive sampling. Data were collected through speaking performance tests in delivering news before and after the implementation of audiovisual media. Data analysis was conducted using descriptive statistics, normality tests, and Paired Sample t-Test with IBM SPSS Statistics. The results showed that the average pretest score was 60.10, while the average posttest score increased to 79.65. The normality test indicated that both pretest and posttest data were normally distributed with significance values of 0.413 and 0.402, respectively. Furthermore, the Paired Sample t-Test yielded a significance value of 0.000 < 0.05, indicating a significant effect of audiovisual media on students' speaking skills in delivering news. Therefore, audiovisual media can be used as an effective learning medium to improve students' speaking skills.